The difference in saliva pH before and after brushing with fluoride containing toothpaste and without toothpaste - Setiawan, Samuel; Haroen, Edeh Rolleta; Hadidjah, Dede (Padjadjaran Journal of Dentistry, 2008)
In administering fluoride through drinking water there is the risk of overdose, higher cost and inadequate availability of drinking water containing fluoride in developing countries like Indonesia. A safe fluoride source is contained in toothpaste. The purpose of this research was to obtain data concerning difference in saliva pH before and after brushing with toothpaste containing fluoride and without toothpaste. The research method used was the quasi-experimental method. Samples were collected by the way of purposive sampling, conducted on 43 male and female research subjects. The data were analyzed by statistical analysis using the t test at 95% confidence level. In this research a control group consisting of 43 people was used. Research results indicated that the average saliva pH before brushing was 7.174; after brushing with fluoride containing toothpaste salivary pH was 7.593. Result research of brushing without toothpaste showed an average saliva of 7.163 before brushing and 7.379 after brushing without toothpaste. The average changes in saliva pH before and after brushing using fluoride containing toothpaste was 0.216. The conclusion of this research was that there was significant difference in saliva pH before and after brushing with toothpaste containing fluoride; there was significant difference in saliva pH before and after brushing without toothpaste, and there was significant difference in saliva pH before and after brushing with toothpaste containing fluoride and without toothpaste.